2021
DOI: 10.33448/rsd-v10i11.19944
|View full text |Cite
|
Sign up to set email alerts
|

Processos enzimáticos na biorremediação e fitorremediação de petróleo em sedimentos de manguezal: uma revisão

Abstract: Diversos vazamentos de petróleo em mares e oceanos ocorreram nas últimas décadas, afetando principalmente estuários e manguezais. Acidentes ambientais envolvendo o petróleo, seus derivados e os resíduos gerados têm sido uma preocupação crescente, por conta dos hidrocarbonetos do petróleo ser considerados contaminantes orgânicos tóxicos e de difícil degradação. Os avanços biotecnológicos têm levado os pesquisadores a adotar a biorremediação e fitorremediação como alternativas potencialmente eficazes para solos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 82 publications
(68 reference statements)
0
0
0
1
Order By: Relevance
“…Phytoremediation (phyto= plant; remediation= treatment) is a sustainable technique that applies elements of the local flora to treat and purify contaminated environments developed in 1991 (Hernández-Valencia et al, 2017). Lacerda et al (2021), Lazaro (2020), Silva (2019), and Mota (2021) demonstrated that this technique yielded satisfactory results and proved that several plant species of high genetic potential can extract, stabilize or immobilize a series of contaminants of environmental concern, such as potentially toxic metals, oil, and domestic and industrial sewage. These authors stated that these plants can proactively absorb highly toxic elements, degrading, metabolizing, or slowing down substances threatening the environment and health of living beings.…”
Section: Introductionmentioning
confidence: 99%
“…Phytoremediation (phyto= plant; remediation= treatment) is a sustainable technique that applies elements of the local flora to treat and purify contaminated environments developed in 1991 (Hernández-Valencia et al, 2017). Lacerda et al (2021), Lazaro (2020), Silva (2019), and Mota (2021) demonstrated that this technique yielded satisfactory results and proved that several plant species of high genetic potential can extract, stabilize or immobilize a series of contaminants of environmental concern, such as potentially toxic metals, oil, and domestic and industrial sewage. These authors stated that these plants can proactively absorb highly toxic elements, degrading, metabolizing, or slowing down substances threatening the environment and health of living beings.…”
Section: Introductionmentioning
confidence: 99%
“… Lacerda et al (2021). mostram que a biorremediação pode ser uma tecnologia utilizada para substituir técnicas empregadas em remediação in situ (como exemplo da barreira reativa) e ex situ (dessorção térmica, incineração e outros) devido a sua capacidade de sustentabilidade.Os EM em estudo mostraram sua capacidade e eficiência em ser usado como biorremediador.…”
unclassified